Evaluating ESG performance: The influence of firm size and gender diversity - Raúl Gómez Martínez; Maria Luisa Medrano-Garcia; Daniel Amo Navas (Small Business International Review, 2024)
This study examines the relationship between firm size and Environmental, Social, and Governance (ESG) scores, with a focus on the growing importance of sustainability and corporate social responsibility (CSR). Drawing on data from 4,525 U.S. companies, an Ordinary Least Squares (OLS) regression analysis reveals a significant positive association between firm size and ESG performance, suggesting that larger firms are better positioned to allocate resources toward sustainability initiatives. Furthermore, the findings indicate that board gender diversity has a positive impact on ESG scores, underscoring the importance of diverse perspectives in corporate governance. The results highlight the need for standardized ESG reporting and provide insights into how firm characteristics shape sustainability outcomes. This research offers practical guidance for corporate leaders and policymakers seeking to advance sustainability practices across organizations.